Cytotoxic properties and complete nuclear magnetic resonance assignment of isolated xanthones from the root of Garcinia cowa Roxb. - Wahyuni, Fatma Sri; Shaari, Khozirah; Stanslas, Johnson; Lajis, Md. Nordin; Hamidi, Dachriyanus (Wolters Kluwer - Medknow Publications and Media, 2016)
Objective: To isolate compounds from the roots of Garcinia cowa and to evaluated their cytotoxic activity against breast (MCF-7), prostate (DU-145), and lung (H-460) cell lines.